La Gestión del Diseño Estratégico, basado en un modelo de la iconografía textil de la cultura Puruhá aplicado a revestimientos cerámicos - Fiallos Baldeón, Luis Miguel (2023)
Currently, the Ecuadorian flat ceramic industry is developing with the innovation of its processes and products. Design emerges as a conceptual strategic element for the creation of ceramic products. An integrative mindset of skills and the combination of critical thinking and creativity. All its methodological structure leads to determining a recurring model for companies in this sector, since the design process is immersed in the production processes in order to obtain better performance results, functions and responsibilities. Design and its management have a broad participation in the quality of the ceramic product, in the sense of providing the products with their own personal identity for an increasingly demanding client. Under this context, the need arises to look for representative aspects to build a graphic culture and it can be thought that design in its different aspects and manifestations of creation are always developed in a sociocultural context. The design of cultural processes and cultural approaches to design from an approach that articulates design and anthropology, can be understood in the sense that designs have in different contexts. In Ecuador, a multiplicity of ethnic groups and cultures coexist, with more or less tension, which account for their diversity. One of the cultures is the Puruhá and the xvi various manifestations that it has expressed in its customs, gastronomy, beliefs, clothing, among others, account for the ancestral legacy that it possesses and its textile iconographic design evidences it. Given the complexity and richness that the image analysis method implies, a strategic design management model is proposed where it is highlighted how the designer can use and reformulate his entire participatory environment in the ceramic sector.